The cinematography of Roger Corman : exploitation filmaker or auteur? - Aleksandrowicz, Pawel (Cambridge Scholars Publishing, 2016)
Roger Corman is an ambiguous artistic figure. On the one hand, he is notorious for shooting and producing his films quickly, cheaply and with blatant disregard for safety measures, which, together with his ability to issue a dozen new films every year and his impressive filmography, have earned him the titles of "shlockmeister" and "the King of the B's" among film journalists. On the other hand, he became the youngest American director to be given a film retrospective at the prestigious Cinématèque Française in Paris, one of his directorial efforts - House of Usher - was selected for preservat